Overview of Mother Characteristic and Condition of Low Birth Weight Babies in the Perinatology Room of RSI Pekajangan - A Almunisah; Emi Nurlaela (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Low Birth Weight Babies are one of the contributing factors to infant mortality, especially during the perinatal period.The study was to describe the characteristics of mother and the condition of low birt weight babies in the perinatology room of RSI PKU Muhammadiyah Pekajangan. This study used a descriptive method with data collection from medical record totaling 88 data for low birth weight babies. Result the characteristics of mother who gave birth to low birth weight babies are the majority age 20-35 years 72 data (81,8%) work as a housewife 48 data (54,5%) father’s occupation as labor 33 data (37,5%). The mother”s last education was high school, but there 24 data (27,3%) educated at university. Pregnancy interval more than 2 years 67 data (76,2%) multiparity 50 data (56,8%) having a history of anemia 3 data (3,4%) and history of hypertension 17 data (19,3%). The baby”s condition included 84 data of LBW (95,5%) asphyxia and respiratory distress 15 data (17%) gestational age >37 weeks 55 data (62,5%) joundice 9 data (10,2%) hypoglycemia 23 data (26,1%) congenital abnormalities one data (1,1%) infant mortality 4 data (4,6%) seizures one data (1,1%) and LBW with anemia 3 data (3,4%).Suggestion : Nurses in the Perinatology Room should provide health education to mothers who have LBW for the prevention of LBW by improving the nutrition of pregnant women and preventing multiparas.